2019
DOI: 10.1016/j.celrep.2019.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Projections from Perirhinal and Postrhinal Cortices Suggest a Multisensory Nature of Lateral, but Not Medial, Entorhinal Cortex

Abstract: Highlights d Postrhinal cortex preferably targets lateral instead of medial entorhinal cortex d Postrhinal and perirhinal projections converge on lateral entorhinal layer 2 cells d Lateral entorhinal cortex is the main parahippocampal multimodal integrative area d A comparable input organization scheme likely exists in the primate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 94 publications
9
100
0
Order By: Relevance
“…A potential center for the integration of egocentric and allocentric spatial information in the rat brain is the POR: this structure projects strongly to the MEC that engages in the encoding of information of an allocentric spatial map (Burwell and Amaral, 1998b;Burwell, 2000;Wang et al, 2020). The POR also projects to the LEC, which is involved in the encoding of an egocentric spatial map and in object recognition memory (Burwell, 2000;Wang et al, 2018;Doan et al, 2019;LaChance et al, 2019). These studies support that the POR may act as a conduit for spatial information processing directed to both entorhinal subdivisions (Winters et al, 2004;LaChance et al, 2019).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…A potential center for the integration of egocentric and allocentric spatial information in the rat brain is the POR: this structure projects strongly to the MEC that engages in the encoding of information of an allocentric spatial map (Burwell and Amaral, 1998b;Burwell, 2000;Wang et al, 2020). The POR also projects to the LEC, which is involved in the encoding of an egocentric spatial map and in object recognition memory (Burwell, 2000;Wang et al, 2018;Doan et al, 2019;LaChance et al, 2019). These studies support that the POR may act as a conduit for spatial information processing directed to both entorhinal subdivisions (Winters et al, 2004;LaChance et al, 2019).…”
Section: Introductionmentioning
confidence: 67%
“…Another study examining the POR supports a role for this structure in visual object discrimination (Furtak et al, 2012). The POR projects to both entorhinal cortices and a recent electrophysiological study suggests that LEC layer 2 receives input from POR and projections towards the MEC from POR are less prominent than previously suggested (Burwell and Amaral, 1998a,b;Doan et al, 2019). Furthermore, the POR is believed to receive information about items from the PRC to integrate a contextual representation (Heimer-McGinn et al, 2017;Park et al, 2017;Burke et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This effect is likely driven by the variable connectivity of the hippocampus to the surrounding isocortex along the anterior-posterior axis, rather than anterior-posterior variations in intrinsic connectivity of the hippocampus proper. Projections from the parahippocampus to the entorhinal cortex, subiculum and CA1 are clearly stratified into anterior (perirhinal) and posterior (postrhinal) tracts in the rodent brain 87,88 , which however converge as early as the lateral entorhinal cortex 89 . In line with this evidence, recent neuroimaging studies have shown more variability in rs-fMRI connectivity between anterior-posterior aspects of the MTL than between hippocampal subfields 90 and that subregions of the parahippocampal and entorhinal cortex exhibit preferential connectivity to either anterior or posterior aspects of the subiculum 44 .…”
Section: Discussionmentioning
confidence: 99%
“…visual) [Bieler et al, 2017; Maruyama & Komai, 2018], which could be a result of connectivity between primary sensory cortices [Stehberg, Dang, & Frostig, 2014]. In addition to primary unisensory cortices and their overlapping border regions, studies have identified the cerebellum [Ishikawa, Shimuta, & Häusser, 2015], insula [Rodgers et al, 2008], parietal cortex [Brett‐Green et al, 2003; Lippert et al, 2013; Menzel & Barth, 2005], prefrontal cortex [Lipton et al, 1999; Reid et al, 2014], perirhinal cortex [Jacklin, Cloke, Potvin, Garrett, & Winters, 2016], and the lateral entorhinal cortex [Doan, Lagartos‐Donate, Nilssen, Ohara, & Witter, 2019], as hubs for multisensory integration in rats. In addition to these cortical structures, studies in rats have also investigated the role of the superior colliculus (SC) in multisensory function on both the neural and behavioral level [Gharaei et al, 2018; Hirokawa et al, 2011; Lau et al, 2018; May, 2006; Sparks & Hartwich‐Young, 1989].…”
Section: Multisensory Studies In Ratsmentioning
confidence: 99%